Improving of Welfare Mustahik Through the Dompet Dhuafa Livestock Center Program - Lubis, Haniah; Harlina, Yuni; Arifin, Zainal; Safi'i, Agus (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This research is motivated by zakat-based economic empowerment in helping to improve the welfare of mustahik. The purpose of this study was to determine the role of zakat carried out by Dompet Dhuafa Riau through the Livestock Center program in improving the welfare of mustahik and to determine the supporting and inhibiting factors in the distribution of zakat. This study is a field study, on mustahik recipients of the Livestock Center Program in Simpang Petai Village, Rumbio Jaya District, Kampar and the Dompet Dhuafa Riau Zakat Institution. The population in this study were the person in charge of the Dompet Dhuafa Riau Livestock Center program and 6 mustahik of the Dompet Dhuafa Riau Livestock Center program. The source of research data uses primary data, which comes from interviews and secondary data through documentation data. The data analysis used is qualitative data analysis, by classifying data collected from the field, then managed and analyzed and described in detail and clearly. The results of the study indicate that the distribution of zakat through the Livestock Center program has had a positive impact and helped improve the welfare of mustahik. Supporting factors in the Livestock Center program are the availability of funds and capital from zakat, training and supervision from Dompet Dhuafa and the interest of mustahik in raising livestock. Inhibiting factors, lack of understanding and experience in raising livestock, patience of mustahik in running the program, and unstable marketing of livestock products.